Biological pretreatment with white rot fungi for preparing hierarchical porous carbon from Banlangen residues with high performance for supercapacitors and dye adsorption - Kong, Wen; Zhang, Xinyu; Fu, Xiao; Zhou, Can; Fan, Linjiang; Zhang, Wanju (Frontiers in Microbiology, 2024)
White rot fungi possess superior infiltrability and biodegradability on lignocellulosic substrates, allowing them to form tailored microstructures which are conducive to efficient carbonization and chemical activation. The present research employed white rot fungus pretreatment as a viable approach for preparing porous carbon from Banlangen residues. The resultant F-A-BLGR-PC prepared by pretreating Banlangen residues with white rot fungi followed by carbonization and activation has a hierarchical porous structure with a high specific surface area of 898 m2 g−1, which is 43.4% greater than that of the unprocessed sample (R-BLGR-PC). When used as an electrode for supercapacitors, the F-A-BLGR-PC demonstrated a high specific capacitance of 308 F g−1 at 0.5 A g-1 in 6 M KOH electrolyte in three-electrode configuration. Moreover, the F-A-BLGR-PC based symmetric supercapacitor device achieved a superb cyclic stability with no obvious capacitance decay after 20,000 cycles at 5 A g−1 in 1 M Na2SO4 electrolyte. Additionally, the F-A-BLGR-PC sample was found to be an ideal adsorbent for removing methyl orange (MO) from water, exhibiting an adsorption ability of 173.4 mg g−1 and a maximum removal rate of 86.6%. This study offers a promising method for the preparation of a porous carbon with a high specific surface area in a biological way using white rot fungi pretreatment, and the derived carbon can not only be applied in energy storage but also in environmental remediation, catalysis, and so on.